STUDI KONFLIK LALU LINTAS SEBAGAI ALAT MENGEVALUASI PENGATURAN LALU LINTAS: (STUDI KASUS SATU SIMPANG-T DI KOTA BANDUNG) - Greece Maria Lawalata (Jurnal Jalan-Jembatan, 2010)
Road improvement program such as geometric intersection improvement or traffic light should consider road safety and accessibility. Those could be evaluated in a short phase without waiting any accident data from police department or accident occurence but using the tool of traffic conflict study. With the tool, the effectiveness of road improvement program could be valued and evaluated. Traffic conflict study is a traffic event which two or more vehicles involved, and those vehicles take evasive act to avoid crashes. In Indonesia, traffic conflict has been used sevral times i.e. for motorcyle facilicty at intersection, intersection improvement, and traffic management at intersection. This paper describes traffic conflict application at one T-intersection to evaluate conflict resulting from the presence of an illegal traffic office (PTR). The method is comparing some conflict with and without PTR. The result showed taht the presence of OTR do not significantly influence on the number of severe and simple conflicts. In terms of conflict category, the major conflict is generated by turning movement to the right (conclict 1), conflict avoiding vechicles turning right on the same road lane (conflict 4), conflict avoiding vehicles turning right from opposite direction (conflict 7). To overcome such problems and to improve capacity, it should be applied an arrow mark for conflict in the same direction to tun right (category 1), and stop sign form conflict avoiding vehicle which turn right in the same road lane (category 4) and conflict avoiding vehicle turn right from opposite direction (category 7). Key words : conflict study, conflict severity, vehicle manouver, T-intersection, traffic volume.